1987
DOI: 10.1111/j.1600-051x.1987.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2 teaching programs on the gingival health of 15‐year‐old schoolchildren

Abstract: The present study evaluated the effect of 2 different dental health education programs on schoolchildren's gingival health and identified the subgroups best reached with these programs. The traditional program was the same as the yearly recurrent Dental Health Week (DHW)--comprising an informational package submitted to the teachers. The comprehensive program was in addition to the DHW-package, based on principles in social learning theory and research. Data from 15 schools in 5 municipalities, comprising 1167… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
6
1
2
Order By: Relevance
“…No significant differences between the sexes were observed in our study. This is in contrast to the general observation that females tend to show more compliance with recommended behavior than do boys (15,16,(30)(31)(32)(33)(34). Thi,s finding may reflect the "collective" approaeh of the programs, which is believed to produce a "leveling out" effect between the sexe,' i (34), While the levels of knowledge observed in our test groups are difficult to compare with other studies due to the different approaches used in the assessment of this variable, some of the observations concerning behavior lend themselves to such comparisons.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…No significant differences between the sexes were observed in our study. This is in contrast to the general observation that females tend to show more compliance with recommended behavior than do boys (15,16,(30)(31)(32)(33)(34). Thi,s finding may reflect the "collective" approaeh of the programs, which is believed to produce a "leveling out" effect between the sexe,' i (34), While the levels of knowledge observed in our test groups are difficult to compare with other studies due to the different approaches used in the assessment of this variable, some of the observations concerning behavior lend themselves to such comparisons.…”
Section: Discussioncontrasting
confidence: 93%
“…There was a general finding in the present study that belter results eoncerning both knowledge and reported behavior were obtained by the more eomprehensive program. This is in accordance with other studies aiming at improving health behavior (15,19,20,29,30), Th« design of the study does not allow assessment of the relative importance of the different eomponents of the comprehensive program. Thus, the time of exposure per se might have had an impact.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the present study were in accordance with other studies aiming at improved knowledge and health behavior. [12–14] The results were also in accordance with the study conducted by Buischi et al , wherein the effect upon dental health knowledge and dental health behavior of a comprehensive and a less comprehensive preventive program was compared in a 3-year follow-up study. In the above study, gender comparison was also done and the difference in knowledge gained was found to be statistically nonsignificant.…”
Section: Discussionsupporting
confidence: 87%
“…The principles of social learning theory in oral health promotion for adolescents were applied in the study by Søgaard et al 29 …”
Section: Resultsmentioning
confidence: 99%
“…. The results showed that children from a lower socioeconomic class benefited more from theory‐based interventions, whereas their counterparts from a high socioeconomic background were able to take advantage of the traditional programme 29 .…”
Section: Resultsmentioning
confidence: 99%